Pengaruh Perbedaan Ketebalan Media Filtrasi Pasir Sungai dan Arang Sekam Padi pada Penurunan Fosfat Air Limbah - Calista, Alferina Vania Widya; Badriani, Ririn Endah; Fildzah, Cantika Almas (Universitas Trunojoyo Madura, 2024)
WWTP Effluent at Regional Hospital (RSD) dr. Soebandi has not fullfilled quality standard of phosphate which is 3 mg/L. This study aims to determine the efficiency of removal phosphate levels and to determine the effect of variations in the thickness of the filtration media reducing phosphate levels in wastewater from hospital wastewater. Method in this research used a Slow Sand Filter Sandwich system with several variables. The thickness ratio of rice husk charcoal and river sand were (R1) 25:5 cm, (R2) 22,5:7,5 cm, (R3) 20:10 cm, (R4) 17,5:12,5 cm and (R5) 0:0 cm. Variations of time used were 120 and 180 minutes. The lowest and highest efficiency was found in reactor 1 (R1) with 120 minutes for contact time at 0% and reactor 4 (R4) with 180 minutes for contact time by 53%. P-value of rice husk charcoal, river sand and contact time is 0,05 that means it have a significant effect on phosphate concentration reduction. T-test result showed significant differences (p-value 0,05), reactors 1 4, reactors 1 5, reactors 2 4, and reactors 2 5.